Pengaruh pendidikan kewirausahaan dan dukungan keluarga terhadap minat berwirausaha di kalangan Gen Z - Sitohang, Mizael Demak; Sinaga, Epelima; Banjarnahor, Yehezkiel Exaudi; Lumbantungkup, Yohana; Manalu, Mawarni Marlina; Tambunan, Khairuddin Ependi (Universitas Negeri Surabaya, 2026)
Unemployment among Generation Z is a serious problem that has resulted in increasing poverty rates and weakening labor competitiveness. The purpose of this study is to examine the impact of entrepreneurship education and family support on the entrepreneurial interest of Generation Z students. This study uses a quantitative approach with data collection through a Google Form-based questionnaire. A total of 80 students from the Faculty of Economics, State University of Medan were sampled using a simple random sampling method. Data analysis was performed using multiple linear regression using SPSS version 25. The research findings indicate that entrepreneurship education has a positive and significant impact on entrepreneurial interest, as well as family support which has been shown to have a similar effect. Both independent variables together have a significant influence on changes in entrepreneurial interest. This finding emphasizes the need to strengthen practice-oriented entrepreneurship education and family support to encourage the emergence of young entrepreneurs.